1953
DOI: 10.1161/01.cir.8.6.849
|View full text |Cite
|
Sign up to set email alerts
|

Problems in the Diagnosis and Surgical Treatment of Pulmonic Stenosis with Intact Ventricular Septum

Abstract: Obstruction to pulmonary blood flow may occur in the pulmonic valve, in the infundibulum or in both. Cardiac catheterization aids in the determination of the site of obstruction. Criteria for the differentiation at operation of valvular and infundibular pulmonic stenosis are enumerated, and the usefulness of accurate pressure tracings during operation is emphasized. The accurate identification of the site or sites of obstruction to pulmonary blood flow is essential to proper surgical management. A correctly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

1954
1954
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…systolic pressure of 100 mm. though Kirklin et al (1953), Blount et al (1954, and Brock (personal communication) thought that a pressure of 75 (or a gradient of 55 mm.) was enough to demand operation.…”
Section: Discussionmentioning
confidence: 99%
“…systolic pressure of 100 mm. though Kirklin et al (1953), Blount et al (1954, and Brock (personal communication) thought that a pressure of 75 (or a gradient of 55 mm.) was enough to demand operation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explain this, Kirklin, Connolly, Ellis, Burchell, Edwards, and Wood (1953) con-cluded that before the development of open heart surgery there were two main reasons: (1) failure to open the valve adequately (they advocated repeated attempts until a satisfactory diminution in the gradient could be demonstrated), and (2) stenosis of the infundibulum due to right ventricular hypertrophy, a hypothesis also suggested by Soulie, Joly, Carlotti, Sicot, and Voci (1952).…”
mentioning
confidence: 99%
“…In order to explain this, Kirklin, Connolly, Ellis, Burchell, Edwards, and Wood (1953) con-cluded that before the development of open heart surgery there were two main reasons: (1) failure to open the valve adequately (they advocated repeated attempts until a satisfactory diminution in the gradient could be demonstrated), and (2) stenosis of the infundibulum due to right ventricular hypertrophy, a hypothesis also suggested by Soulie, Joly, Carlotti, Sicot, and Voci (1952).Introducing the open transarterial operation under hypothermia, Swan and his associates (Swan, Cleveland, Mueller, and Blount, 1954) and Blount, McCord, Mueller, and Swan (1954) obtained a fall in right ventricular pressure to normal and an abolition of the gradient across the pulmonary valve in almost all their cases, assessing them after some months. In a recent review of their later cases (Blount, van Elk, Balchum, and Swan, 1957), they have found that in one-third, approximately, there is a residual gradient three months after operation; they explained this as an infundibular stenosis, which could be obscured by the distal, i.e., valvular, stenosis before operation.…”
mentioning
confidence: 99%
“…It was soon found that this could not always be achieved at operation and for this three main reasons have been suggested. Kirklin et al (1953), reporting twelve cases of transventricular pulmonary valvotomy, discussed the possibility that right ventricular hypertrophy might result in secondary stenosis in the infundibular region. Brock (1955), in an account of control mechanisms in the outflow tract of the right ventricle following a careful study extending over seven years, described and illustrated with pressure records secondary infundibular stenosis after pulmonary valvotomy.…”
mentioning
confidence: 99%